2007
DOI: 10.1111/j.1745-7254.2007.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of multiplexed, microsphere-based flow cytometric assay for multiple human tumor markers

Abstract: Aim: The multiplexed, microsphere-based flow cytometric assay (MFCA) for multiple human tumor markers was established for the early screening and detection of suspected cancer patients. Methods: Covalent coupling of capture antibodies directed against their respective tumor markers to fluorescent microspheres was performed by following the protocols recommended by a commercial corporation with some modifications. The coupling efficiency and cross-reactivity were identified by the Luminex 100 system and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…14 Sputum DNA was prepared and quantified as previously described. 15,16 Viral nucleic acids were extracted using the MiniBEST Viral RNA/DNA Extraction Kit (Ver.5.0; TakaRa, Shiga, Japan) and were then reverse transcribed into cDNA with the TUREscipt 1st Strand cDNA Synthesis Kit (Aidlab Biotechnologies Co., Beijing, China). Supplementary Table 1 shows the limits of detection for each pathogen based on serial dilution.…”
Section: Methodsmentioning
confidence: 99%
“…14 Sputum DNA was prepared and quantified as previously described. 15,16 Viral nucleic acids were extracted using the MiniBEST Viral RNA/DNA Extraction Kit (Ver.5.0; TakaRa, Shiga, Japan) and were then reverse transcribed into cDNA with the TUREscipt 1st Strand cDNA Synthesis Kit (Aidlab Biotechnologies Co., Beijing, China). Supplementary Table 1 shows the limits of detection for each pathogen based on serial dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured for 4 days and then stimulated with LPS or TNF-␣ and IFN-␥ for 48 h. Cell supernatant (50 l) was used to quantify hBf protein expression using a microsphere-based flow cytometric assay developed in house. A monoclonal anti-Bf antibody (1379, a gift from Dr. Joshua Thurman, University of Colorado) was used as a capture antibody by coupling it to region 80 x-MAP beads (Luminex, Austin, TX) as previously described (67). Briefly, 1.25 ϫ 10 5 beads were activated for 20 min in 80 l of activation buffer (0.1 M NaH2PO4 at pH 6.2) containing 10 l each of sulfo-NHS and EDC (each prepared fresh in ddH 2O at 50 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Microsphere-based flow cytometry assays (MFCA) established by Luminex involves a capture antibody coupled covalently to internally dyed polystyrene microspheres. The fluorophores which are red and orange can identify presence of tumor markers, a reporter molecule labeled with a fluorescent marker binds to analyte captured on the bead for detection [106].…”
Section: Cancermentioning
confidence: 99%
“…Table 2 highlights the comparison between reproducibility, upper and lower detection limits, simultaneous multi-analyte detection, sensitivity and accuracy of 5 tumor markers. The results showed that their multiplexed assay was reproducible, sensitive, accurate and compared well with ELISA as a standard assay [106].…”
Section: Cancermentioning
confidence: 99%